Analisa Perencanaan Pajak pada Perusahaan Dagang Kosmetik - Wibawa, Koerniawan Dwi; Kudhori, Ahmad; Kirowati, Dewi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Tax planning is a tax saving measure in accordance with applicable tax laws. Tax planning can be implemented in several ways, one of which is selecting a tax reporting method using PP 55 of 2022, the norms for calculating net income and net profit. The choice of this method must be considered in terms of tax payable and tax risks for the next few years. This study aims to analyze the tax planning that must be carried out by CV ABC. CV ABC is a company located in East Java that focuses on selling women's needs such as skincare, moisturizers, sunscreen, and others. This study is a qualitative study with a descriptive approach. The data collection process involves interviews and documentation. Interviews were conducted with related parties to obtain records and an overview of the business. The records obtained only record incoming and outgoing cash, or can be said to be a cash flow statement that is not categorized based on its activities. The results of the study indicate that CV ABC must use the net profit method for income tax calculations. Several cost components must be considered in preparing fiscal net profit, such as the burden of costs unrelated to the business, a list of asset ownership for recognizing depreciation costs, costs listed on the nominative list, and costs and income included in the final income deduction. CV ABC must eliminate several costs and income, such as food and beverage costs, Wi-Fi, water costs, bank administration fees, and bank interest income. However, taxpayers more often use the PP 55 of 2022 method because it is simpler.